Mechanical and tribological performance of Al-Fe-SiC-Zr hybrid composites produced through powder metallurgy process. (22nd January 2021) - Raghav, G R; Janardhanan, Sheeja; Sajith, E; Chandran, Vidya; Sruthi, V
Abstract: In this work a ternary Al-Fe-SiC metal matrix composites were reinforced using Zr particles through powder metallurgy process. The Al matrix and the reinforcements were mixed in high energy ball mill at a speed of 250 rpm over a period of 5 h so as to develop a homogenously dispersed composite material. The composite powders are then pressed at 500 MPa using hydraulic press. The compressed composite green compacts are then sintered at 500 °C for 2 h and allowed to cool under furnace atmosphere. The densities, micro hardness and compressive strength of Al-Fe-SiC-Zr composites were investigated and reported. The composite materials were characterized using SEM, EDS and XRD. The density of Al-10Fe-10SiC-10Zr hybrid composites was found to be around 3.44 g cm −3 . The Zr particles have influenced the micro hardness of the composite materials. The micro hardness of the Al-10Fe-10SiC-10Zr hybrid composites was found to be better compared to Al-10Fe and Al-10Fe-10SiC hybrid composites. The compressive strength of the Al-10Fe-10SiC-10Zr hybrid composites was around 205 MPa which is 44% higher than the Al-10Fe composite material. The porosity of the hybrid composites has reduced when compared to that of Al-10Fe and Al-10Fe-10SiC hybrid composites. The wear studies reveal that Al-10Fe-10SiC-10Zr bear out better wear resistance. The predominant wear mechanism was identified as adhesive wear followed by plastic deformation. This improved wear resistance was due to the formation of oxides layers such Al2 O3, Fe2 O3 and also due to the presence of AlFe3 and Al3 Zr4 intermetallics.